Verminoside mediates life span extension and alleviates stress in Caenorhabditis elegans. (2nd November 2015) - Pant, A.; Asthana, J.; Yadav, A. K.; Rathor, L.; Srivastava, S.; Gupta, M. M.; Pandey, R.
Abstract: The discovery of bioactive molecules modulating aging in living organism promotes development of natural therapeutics for curing age-related afflictions. The progression in age-related disorders can be attributed to increment in intracellular reactive oxygen species (ROS) and oxidative stress level. To this end, we isolated an iridoid verminoside (VMS) from Stereospermum suaveolens (Roxb.) DC. and evaluated its effect on Caenorhabditis elegans . The present study delineates VMS-mediated alteration of intracellular ROS, oxidative stress, and life span in C. elegans. The different tested doses of VMS (5 μM, 25 μM, and 50 μM) were able to enhance ROS scavenging and extend mean life span in C. elegans . The maximal life span extension was observed in 25 μM VMS, that is, 20.79% ( P < 0.0001) followed by 9.84% ( P < 0.0001) in 5 μM VMS and 8.54% ( P < 0.0001) in 50 μM VMS. VMS was able to alleviate juglone-induced oxidative stress and enhanced thermotolerance in worms. The stress-modulating and ROS-scavenging potential of VMS was validated by increment in mean survival by 29.54% ( P < 0.0001) in VMS-treated oxidative stress hypersensitive mev- 1 mutant strain. Furthermore, VMS modulates expression of DAF-16 (a FoxO transcription factor) promoting stress resistance and longevity. Altogether, our results suggest that VMS attenuates intracellular ROS and stress (oxidative and thermal) level promoting longevity. The longevity and stress modulation can be attributed to VMS-mediated alterations in daf-16 expression which regulates insulin signaling pathway. This study opens doors for development of phytomolecule-based therapeutics for prolonging life span and managing age-related severe disorders.